Input Use Efficiency In The Automotive Industry In Iran, 1984-2013 - Keivani, Farshad Sameni (2018)
This research is about the productivity and efficiency of input in the automotive industry in Iran between1984-2013. Despite the importance of the automotive sector in the non-resource sector, it has faced fluctuating productivity and output. This has been commonly attributed to restrictions in imported inputs because of economic sanctions. This study investigates if input use inefficiency might also be a contributory factor. Towards this end, the study had five specific objectives: (i) To investigate which of the three main production functions, that is, Cobb-Douglas, Constant Elasticity of Substitution or the Translog, appropriately describes the automotive industry in Iran; (ii) To estimate the output elasticity with respect to capital, labour and materials; (iii) To determine the nature of the returns to scale being experienced by the industry; (iv) To evaluate whether or not capital, labour and materials are being used efficiently, and (v) To estimate the elasticity of substitution between the three inputs.